Preparation and optical properties of poly(arylene ether ketone) nanocomposites containing cadmium sulfide nanoparticles. (August 2016) - Hu, Xiyu; Du, Jiahui; Mu, Yongfeng; Hu, Chuhui; Zhang, Shuling; Jiang, Zhenhua
Polymer nanocomposites are usually synthesized by incorporating dried nanoparticles into polymer matrices. This method often leads to aggregation of nanoparticles. In this study, a series of novel poly(arylene ether ketone) (PAEK) nanocomposites containing cadmium sulfide (CdS) nanoparticles were prepared by hydrothermal method with carboxylic-functionalized PAEK (ACA-PAEK) as ligand. The optical characterization of the nanocomposites were carried out using ultraviolet (UV)–visible absorption and photoluminescence spectroscopies, the morphological properties using transmission electron microscopy, and the thermal properties had using differential scanning calorimetry and thermogravimetric analysis. The analyses had shown that CdS quantum dots with diameter of about 4 nm could be synthesized by such route, and the nanocomposites exhibited not only good light emission in the UV range but also excellent heat resistance. In general, a new CdS/ACA-PAEK nanohybrid was synthesized without ligand exchange and had good optical properties and excellent heat resistance.